Does Trading Anonymously Enhance Liquidity? - Dennis, Patrick J.; Sandås, Patrik (Journal of Financial and Quantitative Analysis, 2020)
Is liquidity better when a trade counterparty’s brokerage firm is unknown (anonymous) or known (transparent)? We examine a quasinatural experiment where some firms switched from transparent to anonymous trading and then, 1 year later, switched back. Our results for inside spread, price impact, and limit order book depth suggest that liquidity improves when anonymous post-trade reporting is introduced and liquidity worsens when anonymous post-trade reporting is reversed.